2017
DOI: 10.2217/bmm-2017-0150
|View full text |Cite
|
Sign up to set email alerts
|

Actinin-4 Protein Overexpression as a Predictive Biomarker in Adjuvant Chemotherapy for Resected Lung Adenocarcinoma

Abstract: Aim:Although several clinical trials demonstrated the benefits of platinum-combination adjuvant chemotherapy for stage II-IIIA lung adenocarcinoma, predictive biomarkers for the efficacy of such therapy have not yet been identified. We evaluated protein overexpression of actinin-4 as a predictive biomarker of the efficacy of adjuvant chemotherapy in resected lung adenocarcinoma. Materials & methods: We measured actinin-4 protein levels in patients with completely resected stage II-IIIA lung adenocarcinoma usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Similarly, actinin alpha 4 ( ACTN4) ubiquitous expression in the kidney is also reported in this study to be up-regulated in adhesive small intestine epithelial cells. This is coherent with many studies that reported the overexpression of ACTN4 in diverse biological conditions including diseases (such as cancers) compared to normal controls [ 22 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, actinin alpha 4 ( ACTN4) ubiquitous expression in the kidney is also reported in this study to be up-regulated in adhesive small intestine epithelial cells. This is coherent with many studies that reported the overexpression of ACTN4 in diverse biological conditions including diseases (such as cancers) compared to normal controls [ 22 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Taking into account the experimental data, the authors proposed that the therapy might impair metastatic activity of cancer cells with high ACTN4 expression. This notion was further supported by the following IHC study of lung adenocarcinoma patients after resection of the primary tumor [24]. The results also highlighted the possibility that the patients may benefit from therapy only when tumors exhibit high ACTN4 expression levels.…”
Section: Actn4 As a Predictive Marker For Cancer Developmentmentioning
confidence: 65%
“…Okamoto et al showed that ACTN4 is expressed in small-cell lung cancer (NSCLC) and is obviously related to distant metastasis [16]. Miura et al found that ACTN4 is a promising predictive indicator for the efficacy of adjuvant chemotherapy in NSCLC [17]. In salivary gland carcinoma, ACTN4 expression level was increased and might be a contribute to the poor overall survival of patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…The actinin-4 protein level is closely related to the poor prognosis in human cancers, such as thyroid cancer [13], lung cancer [14,15], and salivary gland carcinoma [16]. Additionally, in lung adenocarcinoma, immunohistochemistry showed that actinin-4 protein is overexpressed and can predict the efficacy of adjuvant chemotherapy for resection [17]. However, the expression of ACTN4 and its clinical outcome in BC has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%